Monochlorotetrazinyl Reactive Dyes: Application to Cotton Fibres - Tutak, Mustafa; Alicilar, Ahmet (Asian Journal of Chemistry, 2011)
By the reaction of tetrazine and triazine groups with the chromophores of three different dyes (reactive blue 4, orange 1 and red 2), monochlorotetrazinyl and dichlorotriazinyl reactive dyes were synthesized. Dyeing yield were examined by applying to cotton fibre with these dyes at different temperatures. Exhaustion and fixation rates (%) were determined by analysis of the washing waters containing waste dye. On comparing the results showed that the exhaustion and fixing efficiencies of monochlorotetrazinyl dyes were lower than those of dichlorotriazinyl dyes although they were generally close to each other.